(NsLABYJ HAOS I KWAZIREGULQRNYE STRUKTURY (B/s - (NsOLDEEW(B, (Nr(B.(Nz(B.s; (NuSIKOW(B, (Nd(B.(Na(B.s; (N~ERNIKOW(B, (Na(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1991)
(NbIBLIOGR(B.: (NS(B. 229-235s
Keywords: (NgAMILXTONOWY SISTEMY (B- (NdINAMIKAs